Prevalence of bullying in school context: a study with school children in a city of Rio de Janeiro (Research, Society and Development, 2022)
Bullying is a multidimensional phenomenon that happens in the school environment and is characterized by repetitive violent actions and power imbalance between aggressor and victim. To reflect upon this topic, this study aimed to investigate the prevalence of bullying in the expressions of the role of victim, role of aggressor and in practices of physical violence. The following groups were compared: boys and girls of different ages (group I: 9, 10 and years old; group II: 12, 13 and 14 years old) and types of school (i.e., public and private). The sample consisted of 325 students: 54,2% were girls and 45,5% were boys from public (83,4%) and private (16,6%) schools from a city in Rio de Janeiro. The instrument used for data collection was the Illinois Bullying Scale. The results showed that boys are more often in the role of aggressors, as they are the ones who practice physical violence more often. In addition, age group II was more frequently in the role of aggressors. Regarding the type of school, the three expressions of bullying practices are more detected in public schools. We emphasize the need for socio-educational actions to prevent violent communication and promote healthy and balanced school relationships which can be protective for the positive development of the entire school community.